a, 2x-3=64
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(2^x=8.64=2^3.2^6=2^9\Rightarrow x=9\)
b) \(3.2^x=48\Rightarrow2^x=16=2^4\Rightarrow x=4\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\Rightarrow2^x=32\Rightarrow2^x=2^5\Rightarrow x=5\)
b) \(\Rightarrow\left(2x+1\right)^3=5^3\)
\(\Rightarrow2x+1=5\Rightarrow x=2\)
c) \(\Rightarrow2^x=32\Rightarrow x=5\)
d) \(\Rightarrow4^3.4^x=4^5\Rightarrow4^x=4^2\Rightarrow x=2\)
e) \(\Rightarrow3^3.3^x=3^5\Rightarrow3^x=3^2\Rightarrow x=2\)
f) \(\Rightarrow7^2.7^x=7^4\Rightarrow7^x=7^2\Rightarrow x=2\)
a. 2x . 4 = 128
<=> 2x + 2 = 27
<=> x + 2 = 7
<=> x = 5
b. (2x + 1)3 = 125
<=> (2x + 1)3 - 53 = 0
<=> (2x + 1 - 5)\(\left[\left(2x+1\right)^2+\left(2x+1\right).5+25\right]=0\)
<=> (2x - 4)(4x2 + 4x + 1 + 10x + 5 + 25) = 0
<=> (2x - 4)(4x2 + 14x + 31) = 0
<=> \(\left[{}\begin{matrix}2x-4=0\\4x^2+14x+31=0\end{matrix}\right.\)
<=> \(\left[{}\begin{matrix}x=2\\VôNghiệm\end{matrix}\right.\)
c. 2x - 26 = 6
<=> 2x = 32
<=> x = 5
d. 64 . 4x = 45
<=> 43 . 4x = 45
<=> 43 + x = 45
<=> 3 + x = 5
<=> x = 2
e. 27 . 3x = 243
<=> 33 . 3x = 35
<=> 33 + x = 35
<=> 3 + x = 5
<=> x = 2
g. 49 . 7x = 2401 (Bn xem lại đề câu này)
<=> 72 . 7x = 74
<=> 72 + x = 74
<=> 2 + x = 4
<=> x = 2
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a.\left(x+5\right)^3=-64\Leftrightarrow x+5=-4\Leftrightarrow x=-9\\ b.\left(2x-3\right)^2=9\Leftrightarrow\left[{}\begin{matrix}2x-3=3\\2x-3=-3\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=3\\x=0\end{matrix}\right.\)
( Nhớ kết luận! )
a.
\(\left(x+5\right)^3=\left(-4\right)^3\)
\(\Leftrightarrow x+5=-4\)
\(\Leftrightarrow x=-9\)
b.
\(\left(2x-3\right)^2=3^2\)
\(\Leftrightarrow\left[{}\begin{matrix}2x-3=3\\2x-3=-3\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}2x=6\\2x=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=3\\x=0\end{matrix}\right.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, 2x-1 = 64
=> 2x-1 = 26
=> x - 1 = 6
=> x = 6 + 1
=> x = 7
b, 32x-10 = 81
=> 32x-10 = 34
=> 2x - 10 = 4
=> 2x = 14
=> x = 7
c, 22x+3 = 1024
=> 22x+3 = 210
=> 2x + 3 = 10
=> 2x = 7
=> x = \(\frac{7}{2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a ) 9 . 3x = 81
3x = 9
x = 3
b ) 2x : 4 = 1
2x = 4
x = 2
c ) 2x - 64 = 2
2x = 66
x = 33
d ) 2x = 16
x = 8
e ) 3 ^ 2 . 3 ^ 4 . 3x = 3 ^ 10
3 ^ ( 2 + 4 + x ) = 3 ^ 10
=> 2 + 4 + x = 10
x = 4
f ) 2x + 4 . 2x = 5 . 2 ^ 5
2x + 8 x = 160
10x = 160
x = 16
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\left(\frac{2x}{3}-3\right)\div\left(-10\right)=\frac{2}{5}\)
\(\Rightarrow\left(\frac{2x}{3}-\frac{9}{3}\right).-\frac{1}{10}=\frac{2}{5}\)
\(\Rightarrow\frac{2x-9}{3}.-\frac{1}{10}=\frac{2}{5}\)
\(\Rightarrow\frac{9-2x}{30}=\frac{2}{5}\Rightarrow\left(9-2x\right).5=60\)
\(\Rightarrow45-10x=60\Rightarrow-10x=15\Rightarrow x=-\frac{15}{10}=-1,5\)
b)\(\left(x+5\right)^3=64\)
\(\Rightarrow\left(x+5\right)^3=4^3\)
\(\Rightarrow x+5=4\Rightarrow x=-1\)
A, 2x/3-3=-4
2x/3=-1
2x=-3
X=-3/2
B,(x+5)^3=4^3
=> x+5=4
X=-1
k nha
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\Leftrightarrow\left(2x+3-2x+5\right)^2=x^2+6x+64\)
=>x^2+6x=0
=>x(x+6)=0
=>x=0 hoặc x=-6
![](https://rs.olm.vn/images/avt/0.png?1311)
a, (2x-3)3 = -64
=> (2x-3)3 = -43
=> 2x-3=-4
=> 2x = -1
=> x = -1 : 2
=> x = -1/2
b, (2x-3)2 =25
=> (2x-3)2 =5^2
=> 2x-3 = 5
=> 2x = 8
=> x = 4
c, (3x-4)2 =36
=> (3x-4)2 =62
=> 3x-4 = 6
=> 3x = 10
=> x = 3.(3)
d, 2x+1 = 64
=> 2x+1 = 26
=> x+1 = 6
=> x = 5
![](https://rs.olm.vn/images/avt/0.png?1311)
a.(x+5)3=-64
x+5=-64:3
x+5=\(\frac{-64}{3}\)
x=\(\frac{-64}{3}-5\)
x=\(\frac{-64}{3}-\frac{15}{3}\)
x=\(\frac{-79}{3}=-26\frac{1}{3}\)
b.(2x-3)2=9
2x-3=9:2
2x-3=\(\frac{9}{2}\)
2x=\(\frac{9}{2}+3\)
2x=\(\frac{15}{2}\)
x=\(\frac{15}{2}:2\)
x=\(\frac{15}{4}\)=\(3\frac{3}{4}\)
a.(x + 5) . 3 = - 64
=> x + 5 = -64 : 3
=> x + 5 = \(-\frac{64}{3}\)
=> x = \(-\frac{64}{3}\) - 5
=> x = \(-\frac{64}{3}\) - \(\frac{15}{3}\)
=> x = \(-\frac{79}{3}\)
b.(2x - 3) . 2 = 9
=> 2x - 3 = 9 : 2
=> 2x - 3 = \(\frac{9}{2}\)
=> 2x = \(\frac{9}{2}\) +3
=> 2x = \(\frac{15}{2}\)
=> x = \(\frac{15}{2}\) : 2
=> x = \(\frac{15}{2}\) . \(\frac{1}{2}\)
=> x = \(\frac{15}{4}\)
HỌC TỐT